An analysis of partitions and strata in Charles Ives's "Three Places in New England". - Frayne, Robert McKee. (University of Ottawa (Canada), 1992)
Three Places in New England contains formal partitions and strata at these partitions. The way Ives organizes musical elements at partitions reveals some of his compositional and structural techniques. This study is specifically directed towards strata in "from The Housatonic at Stockbridge." The strata may be organized according to their respective rhythmic, harmonic, or other appropriate characteristics; in other words, into individually analyzable components. The effect of stratification of musical features, especially similar cohesive features, is a characteristics "Ivesian" trademark. By focusing on partitions, and identifying strata at these points and how they are interrelated, some compositional and structural principles of Ive's style emerge. These principles, utilized by Ives, include (1) tonal reference to chords, scales and (occasionally) progressions in a highly chromatic background, (2) proportional schemes of formal organization of subdivisions within pieces (and a less structured organization of phrase lengths), and (3) the use of passages that have tendencies towards multiple and simultaneous (increased or decreased) parametric changes. (Abstract shortened by UMI.)
Keywords: Music.